Endothelial Barrier and Its Abnormalities in Cardiovascular Disease - Chistiakov, Dimitry A.; Orekhov, Alexander N.; Bobryshev, Yuri V. (Frontiers in Physiology, 2015)
Endothelial cells (ECs) form a unique barrier between the vascular lumen and the vascular wall. In addition, the endothelium is highly metabolically active. In cardiovascular disease such as atherosclerosis and hypertension, normal endothelial function could be severely disturbed leading to endothelial dysfunction that then could progress to complete and irreversible loss of EC functionality and contribute to entire vascular dysfunction. Proatherogenic stimuli such as diabetes, dyslipidemia, and oxidative stress could initiate endothelial dysfunction and in turn vascular dysfunction and lead to the development of atherosclerotic arterial disease, a background for multiple cardiovascular disorders including coronary artery disease, acute coronary syndrome, stroke, and thrombosis. Intercellular junctions between ECs mediate the barrier function. Proinflammatory stimuli destabilize the junctions causing the disruption of the endothelial barrier and increased junctional permeability. This facilitates transendothelial migration of immune cells to the arterial intima and induction of vascular inflammation. Proatherogenic stimuli attack endothelial microtubule function that is regulated by acetylation of tubulin, an essential microtubular constituent. Chemical modification of tubulin caused by cardiometabolic risk factors and oxidative stress leads to reorganization of endothelial microtubules. These changes destabilize vascular integrity and increase permeability, which finally results in increasing cardiovascular risk.